Understanding Remanufacturing Business in Indonesia: Insights from an Initial Survey - Anityasari, Maria; Fernando, Antonius; Suhariyanto, Tatbita Titin; Sari, Komang Nickita; Kusumawardani, Rindi; Akbar, Reza Aulia (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to investigate the current state and challenges of remanufacturing practices in Indonesia, particularly in the heavy equipment sector, including key barriers and opportunities identification. Methodology: A survey involving 23 companies working in the heavy equipment sector was conducted to gather their remanufacturing practices, challenges, and perspectives. The study examines issues related to definitions, regulations, core availability, and quality assurance of remanufactured items. Results: The survey reveals wide variety and inconsistencies in defining remanufacturing due to the absence of standardized definitions and government regulations. This triggers complexities in business process especially in sourcing high-quality cores and communicating the quality of remanufactured items to consumer. Applications/Originality/Value: The findings highlight the need for future research to create a conducive ecosystem for remanufacturing in Indonesia including regulation and policy development. This study provides valuable insights for enhancing the development of the remanufacturing industry.